Facilitating shrimp (Pandalus borealis) peeling by power ultrasound and proteolytic enzyme. (June 2018) - Dang, Tem Thi; Gringer, Nina; Jessen, Flemming; Olsen, Karsten; Bøknæs, Niels; Nielsen, Pia Louise; Orlien, Vibeke
Abstract: The potential of power ultrasound (24-kHz frequency) as an individual treatment and in combination with proteolytic enzyme to promote the shell-loosening of cold-water shrimp ( Pandalus borealis ) was investigated. Textural properties of shrimp were highly dependent on temperature control during the ultrasonic process (27.6-μm amplitude, 120 min duration and 0.9-s pulse), while the peelability of shrimp monitored as peeling work, meat yield and proportion of completely peeled shrimp were less dependent on the temperature. Increasing amplitude (0–46 μm) and time (0–45 min) of ultrasound prior to enzymatic maturation (0.5% Endocut-03L, 6 h, and 3 °C) increased the peelability of shrimp. The parallel combination of ultrasound and enzyme (18.4-μm amplitude, 0.9-s pulse, 0.5% Endocut-3L, 3-h and 4-h duration, and T  ≤ 5 °C) considerably improved the shrimp peelability without detrimental effect on the texture and color of shrimp. Ultrasound was found to inactivate proteolytic enzyme in solution and to modify the structural properties of shrimp shells. From scanning electron micrographs (SEM), we proposed a mechanism for the ultrasound-enzyme-induced shell-loosening based on ultrasonic shell surface erosion and enzyme diffusion. Cavitation bubbles generated from sound waves pitted the surface of shrimp shell, generating pathways for enzyme diffusion into the muscle-shell attachment. Industrial relevance: The shrimp industry is seeking green alternatives to the conventional shell-loosening methods i.e., in brine/on ice maturations. The present study provides an investigation regarding the efficiency of power ultrasound with and without combination with proteolytic enzyme to enhance the shell-loosening and therefore improve the peelability. The findings show that ultrasound is a potential technique for shell-loosening and its efficiency is highest when simultaneously combined with enzyme. Ultrasound introduces spiral pathways in the shell and accelerates diffusion of enzyme through the pathways into the muscle-shell attachment. Thus, the use of simultaneous ultrasound-enzyme combination will shorten the shell-loosening time as compared to the conventional methods and increase the peelability without compromising the color and texture quality of shrimp. Highlights: Ultrasound and an endoprotease were used to loosen shell from meat of shrimp prior to peeling. Temperature control of ultrasound treatment significantly impacted texture but not peelability of shrimps. Increasing amplitude and time of ultrasound increased peelability of shrimps. Parallel combination of enzymes increased peelability without detrimental effects on texture and color of shrimps. Cavitation bubbles pitted the shrimp shell and generated pathways for enzyme diffusion into muscle-shell attachment.